PENGARUH ARUS KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2015-2018 - Muchriana Muchran; M. Fajrin A. Thaib (Magister Akuntansi, Universitas Atma Jaya Makassar, 2020)
This study aims to analyze the effect of cash flow from operating activities, investment activities, funding activities that have an impact on stock prices and analyze the effect of cash flows from operating activities, investment activities, funding activities simultaneously affecting stock prices. Data analysis methods used are quantitative descriptive analysis and multiple regression analysis. Based on the results of a partial test, the effect of cash flow from operating activities on stock prices has a positive and significant effect, thus the first hypothesis is accepted. Based on the results of a partial test between investment cash flow to stock prices, it was found that cash flow from investment activities was not significant, thus the second hypothesis was rejected. Based on the results of a partial test between the cash flows of funding activities against the stock price, it was found that the funding cash flow was not significant. This can be interpreted that the funding cash flow has no effect on stock prices, thus the third hypothesis is rejected. And the results of simultaneous tests prove that there is a simultaneous influence between cash flow operating activities, investment activities and funding activities on stock prices. Thus the fourth hypothesis is accepted.